Preoperative serum glutathione reductase activity and alpha-fetoprotein level are associated with early postoperative recurrence of hepatocellular carcinoma - Shen Lihong; Shao Lijia; Feng Shengchun (Journal of Laboratory Medicine)
The aim of this study is to investigate the correlation between preoperative serum glutathione reductase (GR) activity, alpha-fetoprotein (AFP) level, and early postoperative recurrence in patients diagnosed with hepatocellular carcinoma (HCC).